2012
DOI: 10.1155/2012/486757
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Constitution, Stress, and Discomfort in the First Trimester

Abstract: The purpose of this study was to explore correlations among constitution, stress, and discomfort symptoms during the first trimester of pregnancy. We adopted a descriptive and correlational research design and collected data from 261 pregnant women during their first trimester in southern Taiwan using structured questionnaires. Results showed that (1) stress was significantly and positively correlated with Yang-Xu, Yin-Xu, and Tan-Shi-Yu-Zhi constitutions, respectively; (2) Yin-Xu and Tan-Shi-Yu-Zhi constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…DMARDs, non-steroidal anti-inflammatory drugs (NSAIDs), steroid hormones, and biologics are typically used to treat RA, but are associated with severe adverse effects, including gastrointestinal lesions, cardiovascular complications, and reproductive toxicity (29). Therefore, the exploitation of plant-derived drugs as anti-RA agents with potent effects and lower toxicity profiles has drawn much attention (30). Matrine is the primary active component of the traditional Chinese medicinal herb Sophora flavescens Ait.…”
Section: Discussionmentioning
confidence: 99%
“…DMARDs, non-steroidal anti-inflammatory drugs (NSAIDs), steroid hormones, and biologics are typically used to treat RA, but are associated with severe adverse effects, including gastrointestinal lesions, cardiovascular complications, and reproductive toxicity (29). Therefore, the exploitation of plant-derived drugs as anti-RA agents with potent effects and lower toxicity profiles has drawn much attention (30). Matrine is the primary active component of the traditional Chinese medicinal herb Sophora flavescens Ait.…”
Section: Discussionmentioning
confidence: 99%
“…The most common somatic discomforts include nausea, vomiting, breast engorgement, feeling tired, increased vaginal discharge, dizziness and emotional ups and downs (Wang et al . ). Commonly, the somatic symptoms are related to psychological distress (Heinrichs et al .…”
Section: Introductionmentioning
confidence: 97%
“…Data from 4 diagnostic methods are analyzed according to TCM theories to form a constitutional diagnosis. Past studies have revealed that the BC is greatly influenced by age, chronic diseases [5,6,7], psychological symptoms, and lifestyle [8]. Constitution identification is the basis of TCM syndrome differentiation.…”
Section: Introductionmentioning
confidence: 99%